Decreasing Risk of Cardiovascular Disease that Accelalerating with Smoking - Türk, Hayrettin; Karaca, Merve; Akı, Mert (Turkey Health Literacy Journal, 2021)
Cardiovascular diseases are the most common cause of death worldwide. Cardiovascular diseases are held responsible %31 of deaths in the world. Similar picture is seen in also Turkey with world. In Turkey, %37 of death are caused by cardiovascular diseases. Most important ones of risk factors for cardiovascular diseases can be counted as unhealthy diet, physical inactivity, smoking and alcohol consumption. Most important characteristic of these factors is that they are modifiable, in other words by making provision against these risk factors, the prevalence of cardiovascular diseases can be reduced and death related to this can be prevented. Smoking which is one of these risk factors, 2-4 times increases the risk of cardiovascular diseases. In addition, smoking also increases risks of chronic obstructive pulmonary disease out of cardiovascular diseases and it also increases risks of especially lung cancer, then bladder, colon, stomach cancers and many other diseases. Therefore, by decreasing smoking rates, mortality and morbidity due to many disease can be prevented and health spending depending on these diseases can be reduced. According to statistics of 2019, proportion of 15 years and older individuals using tobacco every day is detected as %28 in Turkey. By actions to reduce this rate, mortality due to smoking and cardiovascular disease caused smoking is being tried to reduce. It is important that ensuring continuation and working for development of these actions for improvement of public health and reduction of health spending.
Keywords: Smoking, cardiovascular disease, ischemic heart disease, cerebrovascular disease, cessation of smoking, mpower